Membrane–plate transition in leaves as an influence on dietary selectivity and tooth form. Issue 98 (September 2016) - Talebi, Mauricio G.; Sala, Enrico A.; Carvalho, Barbara; Villani, Giovanna M.; Lucas, Peter W.; van Casteren, Adam
Abstract: Primates need accurate sensory signals about food quality to forage efficiently. Current evidence suggests that they target leaf foods based on color at long-range, reinforcing this with post-ingestive sensations relating to leaf toughness evoked during chewing. Selection against tough leaves effectively selects against high fiber content, which in turn gives a greater opportunity of acquiring protein. Here we consider a novel intermediate mechanical factor that could aid a folivore: leaves may transform mechanically from membranes (sheets that cannot maintain their shape under gravitational loads and thus 'flop') early on in development into plates (that can maintain their shape) as they mature. This transformation can be detected visually. Mechanical tests on two species of leaf eaten by southern muriqui monkeys ( Brachyteles arachnoides ) in Southern Atlantic Forest, Brazil, support a membrane-to-plate shift in turgid leaves during their development. A measure of this mechanical transition, termed lambda ( λ ), was found to correlate with both leaf color and toughness, thus supporting a potential role in leaf selection. Muriquis appear to select membranous leaves, but they also eat leaves that are plate-like. We attribute this to the degree of cresting of their molar teeth. A dietary choice restricted to membranous leaves might typify the type of 'fallback' leaf that even frugivorous primates will target because membranes of low toughness are relatively easily chewed. This may be relevant to the diets of hominins because these lack the bladed postcanine teeth seen in mammals with a specialized folivorous diet. We suggest that mammals with such dental adaptations can consume tougher leaf 'plates' than others.